Pengaruh Metode Active Learning terhadap Peningkatan Motivasi dan Kreativitas Peserta Didik di Era Globalisasi - Muhasim Muhasim (LP2M STIT Palapa Nusantara, 2019)
Learning with conventional models with lecture methods is still widely practiced by the instructors, it cannot be said to be successful, the media used are less attractive, still use whiteboards and markers so students are less motivated, so that improvements are needed in accordance with the times. Active Learning method, can be used in changing the conventional way of learning. This method can have an effect on increasing the motivation and creativity, in order to be able to change the behavior of the face the globalization era that occurred along the progress of science and the development of technological information. Based on problems occurred, the researchers are interested in research the influence of active learning to increased motivation and creativity learning learners. Research methods qualitative, descriptive, namely through observation, using approach to data librarianship sourced from books and scientific material that is obtained at one of the Internet. Research results can become a reference in the learning process by either the teacher or learners, because it has given clarity how active learning influences the motivation and creativity of learners in the globalization era.